Selling Guantánamo : Exploding the Propaganda Surrounding America's Most Notorious Military Prison - Hickman, John, 1954- (Book collections on Project MUSE., 2013)
In the aftermath of 9/11, few questioned the political narrative provided by the White House about Guantánamo and the steady stream of prisoners delivered there from half a world away. The Bush administration gave various rationales for the detention of the prisoners captured in the War on Terror: they represented extraordinary threats to the American people, possessed valuable enemy intelligence, and were awaiting prosecution for terrorism or war crimes. Both explicitly and implicitly, journalists, pundits, lawyers, academics, and even released prisoners who authored books about the island prison endorsed elements of the official narrative. In this book, the author exposes the holes in this manufactured story. He shines a spotlight on the critical actors - including Rumsfeld, Cheney, and President Bush himself - and examines how the facts belie the "official" accounts. He chastises the apologists and the critics of the administration, arguing that both failed to see the forest for the trees.